Comprehensive Phenotyping of Dendritic Cells in Cancer Patients by Flow Cytometry. Issue 3 (11th November 2020) - Carenza, Claudia; Franzese, Sara; Calcaterra, Francesca; Mavilio, Domenico; Della Bella, Silvia
Abstract : Dendritic cells (DCs) play a crucial role in the complex interplay between tumor cells and the immune system. During the elimination phase of cancer immunoediting, immunostimulatory DCs are critical for the control of tumor growth. During the escape phase, regulatory DCs sustain tumor tolerance and contribute to the development of the immunosuppressive tumor microenvironment that characterizes this phase. Moreover, increasing evidence indicates that DCs are also critical for the success of cancer immunotherapy. Hence, there is increasing need to fully characterize DC subsets and their activatory/inhibitory profile in cancer patients. In this review, we describe the role played by different DC subsets in the different phases of cancer immunoediting, the function exerted by different activatory and inhibitory molecules expressed on DC surface, and the cytokines produced by distinct DC subsets, in order to provide an overview on the DC features that may be useful to be assessed when dealing with the flow cytometric characterization of DCs in cancer patients. © 2020 International Society for Advancement of Cytometry